The Role of Agriculture in Pakistan’s Economic Development: Challenges and Opportunities in a Globalized Market - Dogar, Ali Haider (Annals of Human and Social Sciences, 2023)
This study explores the role of agriculture in Pakistan’s economic development and its challenges and opportunities in a globalized market. Agriculture is a crucial sector for Pakistan’s economy, playing a significant role in GDP, employment, food security, and exports. Despite its importance, the sector faces numerous challenges, such as outdated technology, infrastructure shortcomings, climate change, and restricted access to global markets. However, there are opportunities for growth through modernization, foreign investment, and improved trade agreements. A qualitative research approach was employed, involving interviews with policymakers and farmers. This was supplemented with the analysis of existing data from government and international reports. The findings indicate that agriculture remains a key driver of Pakistan’s economy, contributing substantially to employment and rural livelihoods. However, the sector is hindered by issues such as obsolete technology, deficient infrastructure, climate-related risks, and limited integration into global markets. To enhance the productivity and global competitiveness of Pakistan’s agricultural sector, the study recommends policy reforms, the development of infrastructure, and the adoption of modern agricultural techniques. These steps could help unlock the sector’s full potential and boost its contribution to economic growth.